THE EFFECT OF CREATIVE GAME METHODS ON LEARNING INTERESTS AND PRE-LITERACY SKILLS AT TK MAMBAUL ULUM SUKOWONOTHE EFFECT OF CREATIVE GAME METHODS ON LEARNING INTERESTS AND PRE-LITERACY SKILLS AT TK MAMBAUL ULUM SUKOWONO - Ningsih Supriati (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This study aims to determine how much influence the creative play method has on learning interest and pre-literacy abilities at the early childhood education level at Kindergarten level. child. The type of research used is quasi-experimental research because here the researcher wants to apply an action or treatment. Students' learning interest which affects pre-literacy skills is measured from the work with the T-Test which is carried out on the average class value of A1 and A2 lines Equal variance not assumed that the Sig (2-tailed) value is 0,000 where the value is < 0.05, it can be said that H0 is rejected, so it can be concluded that there is a significant difference / effect. From the mean difference, it shows that the class A2 score of -24 is greater than A1 of -31.8. This shows that although classes A1 and A2 show the same significant effect, class A2 shows a greater influence. It can be concluded that the application of the creative game method is proven to significantly improve the pre-literacy abilities of Mambaul Ulum Kindergarten students